Strategi untuk mengurangi food waste di tingkat rumah tangga - Nunik Gerda; Etty Riani; Sandra Sukmaning Adji (Jurnal Penelitian Pendidikan IPA, 2023)
Food waste is a common issue in countries around the world and become the global concern that planned in SDGs (Sustainable Development Goals) Number 12. Huge percentage of food waste discarded and low number of recycled shows that the existing fight is not optimal. This research aims to analyse the influence factors and strategies for reducing food waste from small scope of household level using SWOT analysis. Based on the result, the highest strength is the â€œControl and management over food needs by familyâ€ score of 0.357. The weakness is â€œNo proper planning to process food wasteâ€ score of 0.481. The highest opportunity is â€œAbility to recreate leftover food" score of 0.39. and the highest threat is â€œEasy to buy food with affordable price" score of 0.496. SWOT analysis shows that the total value of the Strength (S) is lower than Weaknesses (W) with the difference of -0.312. While the total value of the Opportunities (O) is lower than Threats (T) with the difference of -0.125. So, with this unfavored position, the strategy that will be developed to reduce food waste at the household level is a defensive strategy or also called minimizing weakness to survive against threat.